AGE ASPECTS OF THE FORMATION AND DYNAMICS OF DEVELOPMENT OF EXCESS BODY WEIGHT AND HYPERGLYCEMIA IN PREGNANT WOMEN (PROSPECTIVE EPIDEMIOMONITORING) (Modern American Journal of Medical and Health Sciences, 2025)
Аrterial hypertension (AH) in pregnant women occupies a special place among the pressing issues of modern medicine. It is an integral part of at least two extremely acute medical and social problems today: hypertension in general and the reproductive health of the nation. The main problem of hypertension in pregnant women: the lack of a unified terminology, the use of different classification and criteria for hypertension, tactics of patient management. We tried, on the basis of evidence-based medicine, to present the classification of hypertension in pregnant women and the principles of drug therapy, including emergency care in hypertensive crisis.